A widely tunable dual-wavelength based on a microring resonator filter device - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Tiu, Zian Cheak; Ooi, Shok Ing; Aidit, Siti Nabila; Alizadeh, Farideh; Yupapin, Preecha Promphan (IOP Publishing, 2018)
We demonstrate a stable, tunable dual-wavelength (DW) generated by launching an in-house built supercontinuum (SC) into an add-drop microring resonator (MRR). The MRR is fabricated from a silicon-nitrogen-oxygen substrate. The frequency comb of the filtered SC is obtained with an experimental free spectral range (FSR) from 0.39 to 0.46 nm corresponding to 48.7-57 GHz within the wavelength range 1520-1660 nm. The stability of a generated DW within the ranges 1561.16 and 1561.57 nm over 120 min is examined, where high, stable DW with a very low power fluctuation is achieved. This work has demonstrated the use of waveguide based MRR in the fiber laser system, and a remarkable flat and low power fluctuations frequency comb is achieved using the in-house built SC source and MRR.